Cadmium and Lead Concentrations in Water, Sediment, Fish and Prawn as Indicators of Ecological and Human Health Risk in Santubong Estuary, Malaysia - Adriana, Christopher Lee; Farah Akmal, Idrus; Fazimah, Aziz (Deanship of Scientific Research, The Hashemite University, Jordan, 2021)
Cadmium (Cd) and lead (Pb) are toxic heavy metals with a growing appeal for study due to their ability to bioaccumulate in fish which may pose threat to human health through fish consumption. This study reported the concentration of Cd and Pb in water, sediment, fish, and prawn in Santubong Estuary, Malaysia. Water, sediment, fish (Arius maculatus) and prawn (Fenneropenaeus merguiensis) samples were collected from three rivers namely Buntal, Penambir and Demak. These samples were digested and analyzed using Flame Atomic Absorption Spectrophotometer (FAAS) for the heavy metal contents. The potential ecological and human health risks were assessed by using the bioaccumulation factor (BAF), Geo-accumulation Index (Igeo), Enrichment Factor (EF), Provisional Tolerable Weekly Intake (PTWI), Health Risk Index (HRI) and Health Index (HI). Cd and Pb concentrations in water were within the permissible limits but were above the acceptable limits in sediment as recommended by WHO. The concentration of Cd in A. maculatus was (0.10 - 0.13 mg/kg) while the concentration of Cd in F. merguiensis was (0.11 - 0.15 mg/kg), and these values were below the safety limits set by FAO/WHO and MFA. The concentration of Pb in A. maculatus (0.19-1.46 mg/kg) was also below the safety limits; however, the concentration of Pb in F. merguiensis (1.35-2.97 mg/kg) surpassed these safety limits. The Igeo values were less than one, and EF values ranged between 5 and 20, suggesting that this area is polluted with heavy metals. The BAF values for Cd (0.001 - 0.002 mg/kg) and Pb (0.003 - 0.040 mg/kg) showed that there might be an appreciable chance of bioaccumulation of heavy metals in the fish and prawn. The PTWI of prawn was slightly above the acceptable PTWI of Pb recommended by FAO/WHO (2016). Comparison with the safety limits showed that the continuous consumption of these fish and prawn for a long period would impose bad impacts on health. HRI and HI in both organisms were greater than one, indicating that there were possible adverse effects. Therefore, close monitoring of this area is recommended to minimize the risks of aquatic organism consumption.